Formation of Carbon Nano Onions by Thermo-Mechanical Processing of Graphite Powders - Guler, Omer; Evin, Ertan (Carl Hanser Verlag, 2014)
This study reports on the thermo-mechanical synthesis of carbon nano onions from elemental graphite powders. Initially, amorphous carbon was obtained by high energy ball milling technique from graphite powders. X-ray spectra taken from ball milled samples indicated that the hexagonal graphite, composed of layers, was transformed into the amorphous carbon for a shorter milling time of 5 h by high energy input about 78 times of gravity. Subsequent isothermal annealing of milled graphite powders was conducted at 1400 degrees C for 4 h in Ar gas. It was revealed via investigation of transmission electron microscopy that carbon nano onions were formed after annealing.
Keywords: Materials Testing; Carbon Nano-Onion; Ball milling; TEM; X-ray analysis